2017
DOI: 10.1144/sp457.10
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry and U–Pb SHRIMP zircon geochronology of microgranular enclaves and host granitoids from the South Khasi Hills of the Meghalaya Plateau, NE India: evidence of synchronous mafic–felsic magma mixing–fractionation and diffusion in a post-collision tectonic environment during the Pan-African orogenic cycle

Abstract: Felsic magmatism in the South Khasi Hills of the Meghalaya Plateau, NE India, referred herein as the South Khasi granitoids (SKG: 519.5±9.7 Ma), invariably contains rounded to elongate, fine- to medium-grained, mafic to porphyritic microgranular enclaves (ME: 515±13 Ma) showing sharp to crenulate contacts with the host SKG. Compositions of plagioclase, amphibole and biotite in the ME are slightly distinct or similar to those of the host SKG, which appear re-equilibrated through diffusion mechanisms during part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 118 publications
0
24
0
Order By: Relevance
“…In the north‐eastern Indian Craton, Kumar, Pieru, et al () reported zircon U‐Pb ages of I‐type granites (520 Ma) and associated mafic microgranular enclaves (MMEs; 515 Ma) from the Meghalaya plateau, which is part of the Pan‐African‐Braziliano Orogeny associated with Gondwana amalgamation. Kumar, Rino, et al () suggested that the Palaeozoic granitoids (535‐507 Ma) formed during the late stage of the eastern Gondwana amalgamation during the Pan‐African event (Chatterjee, Bhattacharya, Duarah, & Mazumdar, ). The A2‐type granite (515 Ma) exposed in the Khasi Hills was attributed as a product of extension in the post‐orogenic setting of the Pan‐African event (Majumdar & Dutta, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the north‐eastern Indian Craton, Kumar, Pieru, et al () reported zircon U‐Pb ages of I‐type granites (520 Ma) and associated mafic microgranular enclaves (MMEs; 515 Ma) from the Meghalaya plateau, which is part of the Pan‐African‐Braziliano Orogeny associated with Gondwana amalgamation. Kumar, Rino, et al () suggested that the Palaeozoic granitoids (535‐507 Ma) formed during the late stage of the eastern Gondwana amalgamation during the Pan‐African event (Chatterjee, Bhattacharya, Duarah, & Mazumdar, ). The A2‐type granite (515 Ma) exposed in the Khasi Hills was attributed as a product of extension in the post‐orogenic setting of the Pan‐African event (Majumdar & Dutta, ).…”
Section: Discussionmentioning
confidence: 99%
“…B. Gou et al, 2015;Gu et al, 2013;Guynn, Kapp, Gehrels, & Ding, 2012;Hu, Li, Su, Li, & Yu, 2010;Hu, Li, Wang, Xie, & Wu, 2013;Hu et al, 2015;Johnson, Oliver, Parrish, & Johnson, 2001;Ji et al, 2009;J. King, Harris, Argles, Parrish, & Zhang, 2011;Kumar, Pieru, Rino, & Hayasaka, 2017;Lee & Whitehouse, 2007;C. Li, Xie, Sha, & Dong, 2008;G.…”
Section: Geological Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…These features are reported from different parts of the Bastar Craton (Kumar, Rino, & Pal, and 2004b; Kumar & Rino, ; Pandit & Panigrahi, ; Elangovan, Krishna, Vishwakarma, Hari, & Ram Mohan, ). MEs are also reported in postcollisional granitoids from Mahakoshal belt (Bora, Kumar, Yi, Kim, & Lee, ) and related to Pan‐African Orogeny in south Khasi Hills of Meghalaya Plateau (Kumar & Pieru, ; Kumar, Pieru, Rino, & Hayasaka, ; Kumar, Pieru, Rino, & Lyngdoh, ). In this study, we have systematically documented the field and petrographic features, provided the mineralogical and whole‐rock geochemical data for the ME, syn‐plutonic mafic dyke, mixed zones, and host rock from the Pithora pluton to understand the extent and nature of interaction between the felsic and mafic magmas to quantify the mixing of interacting magmas.…”
Section: Introductionmentioning
confidence: 86%
“…Evidence of magma interactions (Figure 3) favors the coupling of Abbreviations for minerals are based on Whitney and Evans (2010); Amp, amphibole; Bt, biotite; Cpx, clinopyroxene; Grt, garnet; Kfs, Kfeldspar; Pl, plagioclase mixing and fractional crystallization processes leading to simultaneous mixing-fractionation of coeval mafic and felsic magmas (Bora, Kumar, Yi, Kim, & Lee, 2013;Kumar, Pieru, Rino, & Hayasaka, 2017). Positive…”
Section: Petrogenesismentioning
confidence: 99%